Perbandingan Pengetahuan Kesehatan Seksual Remaja Berdasarkan Akses Informasi Digital Dan Konvensional Di Era Digital - Veny Delvia Pombaile; Ika Suherlin; Magdalena Martha Tompunuh; Desak Made Yulianti; Ni Made Dewi Anggraeni; Rina Sulisthia Arbie (Health Information : Jurnal Penelitian, 2026)
Summary: Background: Adolescents are a vulnerable group to sexual health problems due to limited access to accurate information, while in the digital era they obtain information from digital and conventional sources that can affect their level of knowledge. Objective: To analyze the relationship and differences in adolescent sexual health knowledge based on digital and conventional information access. Method: A quantitative cross-sectional study involving 64 seventh grade students of SMP Negeri 12 Kota Gorontalo selected using purposive sampling technique. Data were obtained through a multiple-choice questionnaire with a correct (1) and incorrect (0) scoring, then analyzed univariately and bivariately using the chi-square test (? = 0.05). Results: Digital access showed a higher proportion of good knowledge (63.2%) compared to conventional access which was dominated by poor knowledge (38.4%), with a significant relationship between information sources and knowledge levels (p <0.05). Conclusion: Digital information access is superior to conventional access in improving adolescent sexual health knowledge. Suggestion: Further research is recommended to use a stronger analytical design, expand the location and number of samples, and develop a digital sexual health literacy measurement instrument.